Effect of Heating Temperature on Wear Rate, Tensile Strength, and Crystallinity of Cantula Fiber-Reinforced Magnesium/Hydroxyapatite/ Shellac for Bone Screw Material - Zufar Maulana; Joko Triyono; Wijang Wisnu Raharjo (Universitas Sebelas Maret, 2025)
Bone screws are commonly used together with support plates to stabilize fractured bones. Conventional bone screws are typically made from metals such as stainless steel and titanium due to their superior mechanical properties. However, the use of permanent metallic implants often requires a secondary surgical procedure for removal after the bone has healed. Therefore, recent research has focused on developing biodegradable biomaterials that can gradually degrade within the body, eliminating the need for implant removal. This study investigated the effect of heating temperature on the tensile strength, wear rate, and crystallinity of a magnesium/nano-hydroxyapatite (nano-HA)/shellac/cantala fiber biocomposite. The composite materials were mixed using a blender with a volume ratio of magnesium/nano-HA–shellac/cantala fiber of 50/20/30 and then compacted at a pressure of 300 MPa for 10 minutes. Heat treatment was conducted at temperatures of 100 °C, 120 °C, 140 °C, and 160 °C for two hours. The results showed that the lowest wear rate (0.72 × 10⁻³ mm³/Nm), the highest tensile strength (6.58 MPa), and the highest crystallinity (74.15%) obtained from X-ray diffraction (XRD) analysis were all achieved at a heating temperature of 160 °C, indicating that higher heating temperatures improved the mechanical and structural properties of the biocomposite.